Beryllium film deposition in cavity samples in remote areas of the JET divertor during the 2011–2012 ITER-like wall campaign. (August 2017) - Krat, S.; Mayer, M.; von Toussaint, U.; Coad, P.; Widdowson, A.; Gasparyan, Yu.; Pisarev, A.; ,
Highlights: Deposition in remote areas of JET divertor during first JET-ILW campaign was studied with cavity samples. Rate of Be accumulation during JET-ILW is 35 times slower than the rate of C accumulation during JET-C. Rate of D accumulation is 45 times lower during JET-ILW than during JET-C. Most of particles come into cavity sample from near strike point positions, while some C comes from the backsides of divertor tiles. Sticking probabilities for Be particles are below 0.4. Abstract: Beryllium film deposition was studied with cavity samples in remote areas of the inner and outer JET divertor and below divertor tile 5 during the 2011–2012 campaign with the ITER-like wall. Predominantly beryllium films were formed inside the cavities with some additional carbon, the ratio Be/C was >2. These deposited layers had high D/(Be+C) ratios of about 0.3. The formation of these films is mainly due to sticking of beryllium-containing particles with low sticking coefficients <0.5. The observed surface loss probabilities depend on the position in the divertor. The particles responsible for film deposition originated from the location of in the divertor strike points.